Period-3 Orbits of Sequential Dynamical Systems and Their Relationship to Error-Correcting Codes over Finite Fields - Ulutas, Tugce; Koroglu, Mehmet Emin (SPRINGER JAPAN KK, 2026)
A sequential dynamical system consists of the following data; a finite graph Y with vertex set v1,& mldr;,vn\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$v_1,\ldots ,v_n$$\end{document}, a state set, local update functions, and an update ordering sigma\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\sigma $$\end{document}. We study period-3 orbits of SDSs on the complete graph Kn\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$K_n$$\end{document} with identical local functions. We prove that the maximum number theta n+1\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\theta _{n+1}$$\end{document} of 3-cycles in the phase space equals A3(n,4)\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$A_3(n,4)$$\end{document}, the largest size of a ternary code of length n with minimum Hamming distance at least 4. Our approach reduces the problem to a clique number computation in an explicit graph and yields a direct correspondence with optimal ternary (n, 4)-codes. We also give field-agnostic necessary conditions for prime period-p orbits and discuss extensions over Fp\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\mathbb {F}_p$$\end{document}.
Keywords: Sequential dynamical systems; Periodic orbit; Complete graph; Codes over finite fields; ACYCLIC ORIENTATIONS; MINIMUM DISTANCE; EQUIVALENCE; SIMULATION; ELEMENTS; Mathematics